Karya Seni sebagai Media - Sobur, Alex (Mediator, 2007)
In essence, art is a form of human spirit and cultural expression contained and expressing aesthetic beauty. Art is born from the deepest side of human, encouraged by artist tendency toward beauty—whatever it is. Such encouragement mirrored human instinct provide by God (Allah) to His people. Art is also medium, the process of artisans in fact reflects the process of communication. There are messages to be delivered in art. Without messages, art become no more than a mute art, and therefore, has no meaning at all.